A new species of Metrarabdotos (Bryozoa, Ascophora) from Brazil - Santana, Flávia T.; Ramalho, Laís V.; Gumarães, Carmen P. (Zootaxa, 2009)
Worldwide there are approximately 40 species of Metrarabdotos, only six of which are extant. Among the living species, three were previously recorded from the Brazilian coast: M. unguiculatum, M. tuberosum, and M. gulo, collected from Bahia and Espírito Santo States. There are no records of fossil species of Metrarabdotos from Brazil. This study reports two living Metrarabdotos species, collected from three states in Brazil―Sergipe, Bahia and Espírito Santo. One of the species, M. sergipensis, is new to science. Its morphological features, such as extreme tuberculation of the zooidal frontal shield, add appreciably to the range of morphological disparity known in the genus.Key-words: Brazil, Bryozoa, Metrarabdotosidae, new species, Southwestern Atlantic, taxonomy